Evaluation of immersive user interfaces in virtual reality first person games - Raffaele, Rennan (2019)
This study is part of a master’s dissertation aiming to investigate the immersion of user interfaces in first person games using virtual reality. This evaluation is based on the concepts established by the Diegesis theory. Based on that, a table was created with the identified elements in the games that induce more or less immersion to the player. Through the data collected, a questionnaire was developed to obtain information from developers, designers and players, to evaluate the most and the fewer immersive elements of the interfaces in the games selected. The results showed that the Diegetic and Spatial interfaces are the most immersive for virtual reality first person games, and the less immersive were the Meta and Non-Diegetic interfaces. Thus these results can be important if they influence the creation of games interfaces more immersive, because all players want to be immersed when playing games, in particular when playing in virtual environments.